Accommodation of transpressional strain in the Arabia‐Eurasia collision zone: new constraints from (U‐Th)/He thermochronology in the Alborz mountains, north Iran. Issue 1 (28th January 2013) - Ballato, Paolo; Stockli, Daniel F.; Ghassemi, Mohammad R.; Landgraf, Angela; Strecker, Manfred R.; Hassanzadeh, Jamshid; Friedrich, Anke; Tabatabaei, Saeid H.
<x xml:space="preserve">Abstract</x> [1] The Alborz range of N Iran provides key information on the spatiotemporal evolution and characteristics of the Arabia‐Eurasia continental collision zone. The southwestern Alborz range constitutes a transpressional duplex, which accommodates oblique shortening between Central Iran and the South Caspian Basin. The duplex comprises NW‐striking frontal ramps that are kinematically linked to inherited E‐W‐striking, right‐stepping lateral to obliquely oriented ramps. New zircon and apatite (U‐Th)/He data provide a high‐resolution framework to unravel the evolution of collisional tectonics in this region. Our data record two pulses of fast cooling associated with SW‐directed thrusting across the frontal ramps at ~ 18–14 and 9.5‐7.5 Ma, resulting in the tectonic repetition of a fossil zircon partial retention zone and a cooling pattern with a half U‐shaped geometry. Uniform cooling ages of ~ 7–6 Ma along the southernmost E‐W striking oblique ramp and across its associated NW‐striking frontal ramps suggests that the ramp was reactivated as a master throughgoing, N‐dipping thrust. We interpret this major change in fault kinematics and deformation style to be related to a change in the shortening direction from NE to N/NNE. The reduction in the obliquity of thrusting may indicate the termination of strike‐slip faulting (and possibly thrusting) across the Iranian Plateau, which could have been triggered by an increase in elevation. Furthermore, we suggest that ~ 7‐6‐m.y.‐old S‐directed thrusting predated inception of the westward motion of the South Caspian Basin.